(untitled) (Journal of Preventive and Social Medicine, 2022)
Background: End-stage renal disease (ESRD) patients undergoing maintenance hemodialysis often suffer from malnutrition. The primary objective of the study was to measure the level of serum prealbumin, assess the correlation of serum prealbumin with modified subjective global assessment score and determine a cut-off value for prealbumin that can estimate the nutritional status of the study population with highest accuracy, among ESRD patients under maintenance hemodialysis. Methods: A one year long cross-sectional study from July 2016 to June 2017 was conducted at hemodialysis unit of SSMC & MH, BSMMU, BIRDEM hospital and NIKDU, Dhaka, among 80 maintenance hemodialysis patients. Adult patients over the age of 18 years and on regular (≥2 sessions per week) hemodialysis for more than 3 months without any acute infection were enrolled. Nutritional status of the patients was evaluated using modified subjective global assessment score. Serum prealbumin level was compared with both anthropometric and biochemical parameters, as well as with modified SGA score. Using modified SGA score as gold standard, receiver operating characteristic curve was used to estimate best fitting cut-off value for serum prealbumin for nutritional assessment among ESRD patients under maintenance hemodialysis. Results: Mean age of study population was 52.3 years and 66.3% respondents were male. Most prominent primary renal diseases were diabetic nephropathy (48.8%). According to modified SGA score, 10% of the study population had normal nutritional status and 90% had mild to moderate malnutrition. Mean serum prealbumin was 27.8 mg/dl. Serum prealbumin showed significant negative correlation with age, modified SGA score and triglyceride; significant positive correlation was shown with BMI, serum creatinine and serum albumin. Using receiver operating characteristic curve, 32.6 mg/dl was found to be the best fitting cut-off value for nutritional assessment with 73.6% sensitivity, 62.5% specificity and 72.5% accuracy. Conclusion: Data obtained from this study strongly indicates that serum prealbumin can be used as a marker for nutritional assessment among ESRD patients undergoing maintenance hemodialysis. JOPSOM 2021; 40(2):9-15